Patient self-assessment in discriminating the more obstructed side in nasal breathing. Issue 1 (January 2014) - Chin, D; Malek, J; Pratt, E; Marcells, G; Sacks, R; Harvey, R J
Abstract Background: Correlating patient perception of nasal obstruction sidedness to causative anatomy is important in surgical planning. The accuracy of patient-perceived asymmetry of nasal obstruction, as regards objective measures, is described. Methods: Cross-sectional study of patients undergoing nasal airflow assessment. Unilateral obstruction was assessed using visual analogue scale scores and anterior rhinomanometry, without decongestion. Subjective obstruction asymmetry was defined using either the absolute score difference (right vs left) or the minimal clinically important difference, derived statistically. Correlation between subjective and objective obstruction measures was assessed. Results: In 145 patients (mean age ± standard deviation, 42.8 ± 16.6 years; 54.5 per cent female), objective obstruction was right-sided in 32.4 per cent, left-sided in 36.6 per cent and symmetrical in 31.0 per cent. Subjective perception of obstruction sidedness had a sensitivity and specificity of 86.9 and 41.1 per cent, respectively, using the minimal clinically important difference. Positive predictive value was 59.4 per cent using absolute score difference and 53.7 per cent using minimal clinically important difference. Receiver operator characteristic curve analysis indicated correlation between subjective and objective measures (p < 0.001). Conclusion: Subjective perception of nasal obstruction asymmetry has limited accuracy. Corroboration with objective airway assessment may be helpful in patients whose symptoms are incongruous with clinical findings.